E-031 Treatment of Acute Ischemic Stroke Due to Thrombosis of Stenotic Atherosclerotic Lesions of the Posterior Circulation. (26th July 2014) - Alexander, M; Rebhun, J; Hetts, S; Cooke, D
Abstract : Introduction: Endovascular treatment of intracranial atherosclerotic disease is controversial, and optimal treatment remains unclear. Acute ischemic stroke (AIS) due to thrombosis of an in situ stenosis has undergone little investigation. Infarction from such disease in the posterior circulation causes pronounced morbidity. We reviewed outcomes of patients undergoing endovascular treatment of AIS in the setting of posterior circulatory atheromatous stenosis. Materials and methods: A retrospective review was performed of angiographic and neurointerventional procedures at a tertiary medical center between January 2001 and August 2013. Among patients with posterior circulation stenoses on DSA, those undergoing treatment for AIS were identified. Further review of imaging, history, and clinical data was performed to confirm that identified stenosis was due to atherosclerosis rather than other processes. Patient demographics and modified Rankin scale (mRS) at presentation were recorded, as were time to recanalization. Lesion location, degree of stenosis, length, and presence in a dominant vertebral artery were tabulated. Type of treatment was recorded, including device type, use of thrombolytic agent, and any treatment of the underlying stenosis with angioplasty or stent deployment. Immediate clinical and angiographic results were noted. Follow up data were analyzed for mRS, transient ischemic attack, stroke, death, or other complication. Descriptive statistics were performed to summarise above-described demographic, lesion, and treatment features. Multivariate regression analysis was performed to identify any role of these features in outcomes. Results: 561 patients were identified with posterior circulation stenosis, intracranial or otherwise. 10 patients underwent endovascular treatment of AIS due to thrombosis at a chronic atherosclerotic lesion. 5 women and 5 men were treated. Ages ranged from 38 to 81 years old (mean 55.5, SD 12.6). Presenting mRS was 3 for 7 patients and 4 for 3. Mean time to recanalization was 15.2 h (7.5 to 28 h, SD 7.3). 2 lesions occurred in vertebral arteries, 1 of which was dominant. 8 lesions occurred in the basilar artery. Stenoses were 50–94% (mean 76.6, SD 15.1), while length was 4–40 mm (mean 13.6, SD 10.5). 2 patients were treated with catheter directed thrombolysis alone, 6 were treated with a Merci device, and 2 were treated with a Penumbra suction catheters. 1 patient was treated with angioplasty; 3 were treated with balloon-mounted stents. One atherosclerotic lesion treated with a stent improved from 94 to 50% stenosis; the others had no residual stenosis following angioplasty or stenting. No intraprocedural complications occurred. There were two deaths, both within 4 days of treatment with stents. Mean follow up was 425 days. Of the surviving patients, 3 (37.5%) patients had mRS 0 at last contact. 2 (25.0%) patients had mRS 1, and one each (12.5%) had mRS 2, 3, and 4. No statistically significant effect of feature was identified for outcomes. Conclusion: Endovascular treatment can be performed with high rates of technical success for AIS due to thrombosis at chronic atherosclerotic lesions. In spite of potential for poor outcomes, significant recovery of function is possible following treatment. Further evaluation is warranted to identify those patients most likely to respond to such intervention. Disclosures: M. Alexander: None. J. Rebhun: None. S. Hetts: 1; C; Stryker Neurovascular. 6; C; Stryker Neurovascular, statistical support services. D. Cooke: None.